Two new Nearctic carnid flies of the genus Meoneura Rondani (Diptera: Carnidae) - Stuke, Jens-Hermann; Levesque-Beaudin, Valerie (Zootaxa, 2023)
Meoneura pacifica spec. nov. (USA: Montana) and Meoneura tyrionlannisteri spec. nov. (Canada: British Columbia, USA: Montana) are described, and their DNA barcode provided.